Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1097/00001888-199707000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Insights into medical studentsʼ career choices based on third- and fourth-year studentsʼ focus-group discussions

Abstract: Students' career decisions are complex, dynamic, and individualized processes. The use of qualitative measures helps bolster understanding of these processes by identifying new factors (such as mastery of knowledge) and by further characterizing known factors (such as role models and financial considerations). A comprehensive and valid understanding of students' career-decision making is necessary to develop successful strategies to sustain and encourage the choice of primary care careers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
68
1
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 0 publications
2
68
1
3
Order By: Relevance
“…Factors shown to be associated with choosing family medicine include medical school characteristics, [4][5][6][7][8][9] personal interactions, [10][11][12][13][14][15][16][17] and lifestyle preferences, personal fit and workforce factors, including expected income, prestige, job opportunities, longitudinal care and societal need. 16,[18][19][20][21][22][23] Others have demonstrated that career preference at the time of entering medical school may be a significant predictor of students' eventual career choice. 4,[24][25][26] Colwill, for example, suggests that students usually see themselves as either generalists or specialists at the start of medical school.…”
mentioning
confidence: 99%
“…Factors shown to be associated with choosing family medicine include medical school characteristics, [4][5][6][7][8][9] personal interactions, [10][11][12][13][14][15][16][17] and lifestyle preferences, personal fit and workforce factors, including expected income, prestige, job opportunities, longitudinal care and societal need. 16,[18][19][20][21][22][23] Others have demonstrated that career preference at the time of entering medical school may be a significant predictor of students' eventual career choice. 4,[24][25][26] Colwill, for example, suggests that students usually see themselves as either generalists or specialists at the start of medical school.…”
mentioning
confidence: 99%
“…5,7 The data from the virtual advisor program also support this impression, with nearly 65% of career advisees identifying themselves as either third-or fourth-year medical students. Based on this, one could conclude that how we structure and provide clerkship experiences will be critical to our continued expansion, recruitment, and success within the academic community.…”
mentioning
confidence: 89%
“…Medical students want structure, encouragement, and mentoring from faculty, factors that are often cited as reasons for a particular career choice. 4,5 Other specialties such as internal medicine have demonstrated that a significant independent predictor of specialty selection by excellent medical students is the presence of dedicated, high-quality educators. 6 Studies in general surgery have suggested that a declining interest in surgical careers may be related to students' perceptions of surgeons as having limited interest in medical education and mentorship.…”
mentioning
confidence: 99%
“…2 Major factors that influence the medical students to choose the future specialization are job opportunities, expected income, prestige, life style preferences, risk associated with that specialty, societal appreciation of specialty, gender difference, preclinical and clinical experiences, role models and characteristics of medical college. 3,4,5 There are deficiencies in certain specialties like Psychiatry, ophthalmology and also non specialist doctors to manage primary health centres. 6,7,8 It is observed in studies done in developed countries that life style factors and student education loans are essential factors for medical students to choose certain specialization after under graduation.…”
Section: Introductionmentioning
confidence: 99%